Uniform Reporting of Next Generation Sequencing: Indian Society of Medical and Pediatric Oncology - Anu, R. I.; Patel, Amol; Pathak, Neha; Mehta, Prashant; Chougule, Anuradha; Sheth, Harsh; Veldore, Vidya; Suryavanshi, Moushumi; Gupta, Vineet Govinda; Disel, Umut; K., Tilak T. V. S. V. G.; Dutt, Amit; Sadanandam, Anguraj; Sirohi, Bhawna; Kulkarni, Padmaj (Indian Journal of Medical and Paediatric Oncology, 2025)
Molecular oncology is the cornerstone for diagnosis, treatment, prognosis, and screening of individuals who present to an oncology clinic. The integration of molecular diagnostic techniques with therapeutic management of patients has resulted in unique biomarker development and improved clinical endpoints. Amongst all laboratory diagnostic techniques applied in oncology, next generation sequencing (NGS) of nucleic acids holds cardinal merit in the present day. Multi-omic biomarkers are the mainstay of selecting variation-specific targeted therapy and immunotherapy. Hence, it is essential to utilise the right diagnostic techniques and harmonize their reporting accurately against rigorous quality standards.We aimed to develop a consensus technical standard guideline on quality assurance and reporting of genetic tests that influence clinical decision making in oncology.Under the initiative of Indian Society of Medical and Pediatric Oncology (ISMPO), a working group of national and international subject matter experts including clinicians, scientists, and bioinformaticians was formulated in 2022. Published scientific literature and laboratory technical standards were studied by this panel and a document for the Indian molecular oncology sector was drawn after obtaining consensus on every recommendation from all members of the working group.Guidelines for introducing uniformity in NGS reporting have been developed by a working group comprising of country's leading molecular oncologists, geneticists, and molecular pathologists alongside international experts, under the aegis of the Indian Society of Medical and Pediatric Oncology.The proposed guidelines and recommendations are intended to be used as a framework to standardize NGS reporting across India, which in turn will enable clinicians and allied healthcare professionals to make informed decisions for unparalleled patient care.
Keywords: molecular oncology; next generation sequencing (NGS); liquid biopsy; AMP-ASCO-CAP; ACMG; ESMO; ESCAT